2019
DOI: 10.1007/s42489-019-00018-y
|View full text |Cite
|
Sign up to set email alerts
|

Die kartographische Rekonstruktion der Landschaftsentwicklung des Oberschlesischen Industriegebiets (Polen) und des Ruhrgebiets (Deutschland)

Abstract: Zusammenfassung Zu Beginn des 19. Jahrhunderts zeigte sich die Landschaft in Deutschland und Polen in einem Zustand, der sich seit dem Mittelalter nur wenig verändert hatte. Erst die einsetzende Industrialisierung führte zu einer massiven Umgestaltung der Kulturlandschaft, die charakteristische räumliche Strukturen in den industriellen Zentren des Ruhrgebietes und des Oberschlesischen Industriegebiets hervorbrachte. In einem deutsch-polnischen Gemeinschaftsprojekt wurde nun erstmals das Ausmaß der landschaftli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There were three places in which area of settlement slightly decreased. This could be linked with the increase of settlement area in surroundings which cause the migration of people and change of residence (Medyńska-Gulij et al, 2019). The growing area of settlements affected also water bodies which dried.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were three places in which area of settlement slightly decreased. This could be linked with the increase of settlement area in surroundings which cause the migration of people and change of residence (Medyńska-Gulij et al, 2019). The growing area of settlements affected also water bodies which dried.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, there was a need for manual rubber sheeting (spatial adjustment) of vector data according to Messtischblätter. Our approach was similar to the methods presented by Medyńska-Gulij et al (2019) and suggested by Kraak and Ormeling (2013, p. 95) for processing cartographic source materials form different time periods. This means snapping vectors from the Urmesstischblätter to the Messtischblätter vectors in places where there were distortions.…”
Section: Digitalizationmentioning
confidence: 91%
See 1 more Smart Citation
“…Another important issue is the choice of a research method that will allow experts in cartography and geomatics to express their subjective opinions on the usefulness of the designed visualizations [13]. However, the effectiveness of a visualization for drawing conclusions can also be measured objectively by means of questions answered by the participants [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Historical objects, crucial for the country's history, have been frequently non-existent for centuries, and various sources need to be used to reconstruct them [7,8]. Schematic perspective drawings of buildings, horizontal and vertical maps, as well as situational maps made by scientists to present the hypotheses of the original medieval state constitute significant sources of information.…”
Section: Introductionmentioning
confidence: 99%